Increased amounts of a novel penicillin-binding protein in a strain of methicillin-resistant Staphylococcus aureus exposed to nafcillin. - Chambers, H F (1985)
In addition to the four typical penicillin-binding proteins (PBPs), a strain of heterogeneously methicillin-resistant Staphylococcus aureus produced an extra 78-kD PBP (PBP 2a) that had a low affinity for nafcillin and penicillin. Addition of nafcillin to cultures of this strain caused a rapid increase in the amount of this PBP in cell membranes. This increase occurred at subinhibitory concentrations of drug within minutes of exposure, and was blocked by inhibitors of protein and RNA synthesis. This suggests that the synthesis of PBP 2a can be stimulated by exposure to beta-lactam antibiotics. This process may, in part, explain the heterogeneity in methicillin-resistant S. aureus.